Climatic Water Balance and Groundwater Recharge in Abu-Jir Village, Al-Anbar Governorate, Western Iraq - Al-Dulaimi, Alaa Mustafa Saeed; Al-Kubaisi, Qusai Y. (Iraqi Journal of Science, 2022)
The study area is located in Al-Anbar Governorate, western Iraq. The climatic data were collected from Al-Ramadi Meteorological Station for the period 1990 to  2020 and used to assess the climatic condition of the study area. The total annual rainfall, relative humidity, monthly average temperature, evaporation, wind speed and sunshine duration are 108 mm, 52.7 %, 22.6˚C, 2814.3 mm, 2.2 m/s and 8.8 h/day, respectively. The climate of the study area is described as an arid to sub arid and relatively hot in summer and cold with low rain in winter. During the data used, the highest potential evapotranspiration was 217.1 mm in July, while the lowest value was 10.7 mm in January, with a total amount of 1170.07 mm. The highest and lowest corrected evapotranspiration becomes 264.2 mm in July and 9.4 mm in January, with 1310.3 mm. water Surplus (WS) is 2.1mm, 10.71mm, and 5.65mm in December, January and February, respectively. The WS was 18.46mm, forming 17.09 % of the total annual rainfall. The groundwater recharge (18.46 mm) with a rate of 17.09%  represents the recharge from the total rainfall zero surface runoff. It has been found that the low amount of rain and sandy soil are among the most important factors causing the absence of surface runoff.